Relationship between in-hospital mortality and inflammation markers in COVID-19 patients with the diagnosis of coronary artery disease - Uğur Küçük; Sevil Alkan Çeviker; Alper Şener (Journal of Contemporary Medicine, 2021)
Introduction: Inflammation plays an important role in the basis of coronary artery diseases and their adverse outcomes. Neutrophil-lymphocyte ratio (NLR), Systemic Immune Inflammation Index (SII) and C-reactive protein (CRP) are simple and useful markers that reflect the inflammatory state. Our study evaluated the usability of these markers in predicting in-hospital mortality in patients with COVID-19 with the diagnosis of coronary artery disease. Material and Method: Our study population consisted of 111 (48 male, 63 female) newly diagnosed patients with COVID-19. Neutrophil-lymphocyte ratio (NLR) was estimated using neutrophil (N), and lymphocyte (L) counts and the systemic immune inflammation index SII (NxP / L) was calculated using N, L and platelet (P) values. The relationship of NLR, SII and CRP values with in-hospital mortality was investigated. Results: During the treatment process, 16 patients exited. Any statistically significant intergroup difference was not observed as for SII and NLR values obtained by their use in combination (p = 0.872, p = 0.979, respectively), CRP values were statistically significant in the group with in-hospital mortality (p lt;0.001). In logistic regression analysis, CRP (odds ratio [OR] = 1.078, 95% confidence interval [CI]: 1.0225-1.133, p = 0.003) was associated with in-hospital mortality. In ROC analysis, the cut-off values of 3.1 mg / dL, for CRP were significant with 87% sensitivity and 58% specificity in predicting in-hospital mortality (p lt;0.001). Conclusions: CRP levels are associated with in-hospital mortality in patients with COVID-19 who had also received coronary artery disease with a history of coronary intervention.